2020
DOI: 10.1007/s11149-020-09420-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between capital and liquidity prudential instruments

Abstract: The risks associated with credit and liquidity positions and asset and liability maturity mismatches are mitigated by applying capital ratio, leverage ratio, liquidity coverage ratio and net stable funding ratio requirements to banks. As a macroprudential authority, the Czech National Bank moreover responds to changes in systemic risk by changing the capital buffer requirements. This can induce a reaction by banks leading to a change in their balance-sheet structure, which, in turn, will affect their degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The interactions with the liquidity requirements as suggested by Komárková et al (2020) could not be empirically explored in this paper due to data availability issues. The time series for liquidity regulatory tools (LCR and NSFR) are significantly shorter than for capital adequacy.…”
Section: Solvency Modelmentioning
confidence: 99%
“…The interactions with the liquidity requirements as suggested by Komárková et al (2020) could not be empirically explored in this paper due to data availability issues. The time series for liquidity regulatory tools (LCR and NSFR) are significantly shorter than for capital adequacy.…”
Section: Solvency Modelmentioning
confidence: 99%
“…At the same time, a study by Martin Hodula, Zlatuše Komárková, and Lukáš Pfeifer showed that in the declining phase of the cycle, when the authority relaxes the riskweighted capital requirement, it becomes crucial to monitor how restrictive other instruments are to reduce the risk of a significant decline in lending during a recession, which may occur due to a breach of a capital or liquidity standards [16][17][18].…”
Section: Analyzed Literaturementioning
confidence: 99%
“…The introduction of a leverage ratio requirement in the EU effective from 1 June 2021 had a similar effect. It has led to an increase in the resilience of the banking sector (Pfeifer and Hodula, 2021) and, on the other hand, has led to overlaps between the leverage ratio requirement and macroprudential capital buffers (Pfeifer et al, 2017;ESRB, 2021). Hodula et al (2021) point out some interaction not only between capital requirements (capital and leverage ratio) with each other, but also between capital and liquidity requirements (the liquidity coverage ratio requirement and the net stable funding ratio requirement).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…It has led to an increase in the resilience of the banking sector (Pfeifer and Hodula, 2021) and, on the other hand, has led to overlaps between the leverage ratio requirement and macroprudential capital buffers (Pfeifer et al, 2017;ESRB, 2021). Hodula et al (2021) point out some interaction not only between capital requirements (capital and leverage ratio) with each other, but also between capital and liquidity requirements (the liquidity coverage ratio requirement and the net stable funding ratio requirement). The paper describes and quanti es the additional effect of the introduction of the MREL on the capital surplus and the usability of banks' capital buffers in the Czech banking sector using solvency stress tests.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%